Predictors of cigarette smoking frequency among European adolescents aged 13–15: the critical role of parental smoking and age of initiation. - Dadras, Omid; Abio, Anne (European Child & Adolescent Psychiatry, 2025)
This cross-sectional study investigated predictors of cigarette smoking frequency among European adolescents aged 13–15, focusing on parental smoking, age of initiation, and socioeconomic factors. Data were derived from the Global Youth Tobacco Survey (2020–2023) in eight European countries. Smoking frequency was classified as infrequent (< 1/day), daily light (1/day), moderate (2–5/day), and heavy (> 5/day). Individual variables (age, pocket money, age at initiation, tobacco experimentation), familial factors (parental smoking, parental education), and country-level factors (PPP-adjusted cigarette prices, income inequality) were analyzed using sex-stratified multilevel ordinal logistic regression models, accounting for clustering at the country and school levels. Notable country- and gender-specific variations in smoking prevalence were observed. Notably, Bulgaria and Albania exhibited the highest prevalence of heavy smoking (> 5 cigarettes/day). Overall, girls were more likely to be smokers, while boys tended to be heavy smokers. Older age, early initiation (< 10 years), and tobacco experimentation significantly increased smoking frequency in both sexes. For males, paternal smoking predicted higher frequency (OR = 2.06), whereas maternal smoking appeared protective (OR = 0.67). Among females, maternal smoking and dual parental smoking were associated with increased frequency. Higher pocket money was also associated with smoking frequency, while cigarette affordability showed a marginal inverse association in males. Our findings underscore the critical role of early smoking initiation and parental influence in determining smoking frequency among European adolescents. Tailored interventions addressing familial risk factors and socioeconomic determinants are essential to curb heavy smoking in this vulnerable population.